Basal cell carcinoma and squamous cell carcinoma of the conjunctiva in a single lesion - Melissa A. Trudrung; Cole Bacig; Brandon Vander Zee; Heather Potter (American Journal of Ophthalmology Case Reports)
Introduction: Basal cell carcinoma (BCC) occurrences in the conjunctiva are exceptionally rare. These lesions become exceedingly rarer next to an adjacent area of squamous cell carcinoma. A collision tumor of both basal cell and squamous cell carcinoma is infrequently encountered in the literature. Case presentation: An elderly male patient was evaluated for concern of ocular surface squamous neoplasia on his left conjunctiva. The lesion appeared as a tan-white elevated lesion with atypical vessels in papillary fronds. The patient underwent surgical excision of the lesion, and the tissue was sent to ocular pathology for histopathologic evaluation. The final diagnosis was basal cell carcinoma and squamous cell carcinoma. The two tumors of both basal cell carcinoma and squamous cell carcinoma were juxtaposed with an abrupt transition zone with no fluidity of differentiation. The lesion had typical features for BCC with positive stain for Bcl-2, P63, P53, CD10, and BerEP4. Additionally, the SCC region stained positive for EMA, P63, and P53. Conclusion: We report a single lesion of the conjunctiva with features of both basal cell carcinoma and squamous cell carcinoma. This case report describes a unique case of two independent neoplasms of the conjunctiva. This further adds to the literature of collision tumors to characterize the lesion with appropriate immunohistochemical analysis.